Performance of Copper‐Graphite‐Polytetrafluoroethylene Composites Fabricated by Spark Plasma Sintering and Hydrothermal Impregnation. Issue 45 (1st December 2020) - Jiang, Dafa; Jiang, Zhongcheng; Zhang, Jun; Lin, Ping; Peng, Baolin; Zhang, Haifeng; Liao, Jiapeng; Li, Wang; Zou, Jianpeng
Abstract: Copper‐graphite composites prepared by spark plasma sintering (SPS) were used as raw material to synthesize copper‐graphite‐polytetrafluoroethylene (PTFE) composites via the hydrothermal impregnation of a PTFE emulsion. The microstructure, hydrophobic performance, friction property and interface behavior were systematically studied using scanning electron microscopy (SEM), a surface science comprehensive tester and a friction tester combined with various characterization methods, such as X‐ray diffraction (XRD), a laser particle size analyzer and metallographic microscopy. The results revealed that the copper‐coated graphite was consistent with the diffraction patterns of copper and graphite, and the coated‐copper had uniformly covered the graphite surface with good interface combination. The interface combination worsened with a decrease of the mass fraction of copper in the composites. Moreover, the water contact angle of the copper‐graphite‐PTFE composite of 50 wt. % Cu after PTFE impregnation reached 160°, and was hence superhydrophobic, while the copper‐graphite‐PTFE composite of 45 wt. % Cu exhibited the optimal performance with a friction coefficient, wear rate and resistivity of 0.112, 3.25×10 −3  mm 3 /(N m), and 12×10 −7  Ω m, respectively. PTFE impregnation improved the hydrophobicity and friction‐and‐wear properties of the copper‐graphite composites, and the resulting conductivity could meet the requirements of practical applications. Our results indicated that the content of copper played a crucial part in determining the comprehensive property of copper‐graphite‐PTFE composites. Abstract : The PTFE coating formed via the PTFE‐impregnation into the pores of the copper‐graphite composites under hydrothermal conditions with high temperatures and high pressures. After PTFE impregnation, the contact angle between the copper‐graphite composites and water rose rapidly from 67 °C to 160 °C. The friction coefficients of the copper‐graphite samples after PTFE impregnation were between 0.14 and 0.17, which were lower than those of the copper‐graphite samples before PTFE impregnation.